Knowledge, attitudes, and practices of healthcare workers regarding human immunodeficiency virus index testing in 2021, Burkina Faso - Smaïla Ouedraogo; Ahmed Kabore; Ismaël Diallo; Maurice Sarigda; Désiré L. Dahourou; Kuilga B. Kabre; Issa Romba; Bapougouni P.C. Yonli; Ter T.E. Dah; Nicolas Meda (AOSIS, 2023)
Although knowing one's HIV status is a necessary step in initiating antiretroviral treatment, more than a quarter of Burkinabe who are HIV‑positive do not know their status. To reach the target of screening at least 95% of people living with HIV (PLHIV), the country has opted for HIV index testing (screening of sexual partners, children and partners of intravenous drug users). This study assessed the knowledge, attitudes and practices of health workers on HIV index testing. A cross‑sectional study was conducted among health workers on index testing pilot sites in Burkina Faso. We constructed scores of health workers' knowledge, attitudes and practices regarding HIV index testing. A total of 132 health workers were surveyed, 62.8% of whom were female. Regarding profiles, 44.7% of the participants were nurses and 5.3% were midwives; physicians and psychosocial counselors accounted for 16.7 and 33.3%, respectively. Most of the participants worked in public health centers (60.6%). Overall, the majority of the participants had poor or average knowledge (85.6%) of the index testing strategy and harmful or inadequate practices (87.1%). Less than half (40.9%) had favorable attitudes toward the strategy. Our study showed that the knowledge of health workers was generally average, their attitudes were not very favorable and their practices were mostly inadequate with regard to HIV index testing. In order to increase the chances of reaching the first 95% of UNAIDS, trainings on the topic must be designed for health workers.